2022
DOI: 10.1101/2022.01.13.22269243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited Cross-Variant Immunity after Infection with the SARS-CoV-2 Omicron Variant Without Vaccination

Abstract: SARS-CoV-2 Delta and Omicron strains are the most globally relevant variants of concern (VOCs). While individuals infected with Delta are at risk to develop severe lung disease1, Omicron infection causes less severe disease, mostly upper respiratory symptoms2,3. The question arises whether rampant spread of Omicron could lead to mass immunization, accelerating the end of the pandemic. Here we show that infection with Delta, but not Omicron, induces broad immunity in mice. While sera from Omicron-infected mice … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 41 publications
7
41
0
2
Order By: Relevance
“…We and others have shown that humoral function is significantly boosted in individuals with breakthrough infections after vaccination (Kitchin et al, 2022; Suryawanshi et al, 2022; Walls et al, 2022). This study confirms this is also true of Omicron breakthrough infections, with a 153-fold increase in titers to D614G in vaccinated compared to unvaccinated individuals, consistent with other studies (Khan et al, 2022; Suryawanshi et al, 2022; Zhou et al, 2022). We also extend our previous study, where we showed ADCC was boosted by breakthrough infection, to include ADCP, confirming that this applies to other Fc effector functions (Kitchin et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…We and others have shown that humoral function is significantly boosted in individuals with breakthrough infections after vaccination (Kitchin et al, 2022; Suryawanshi et al, 2022; Walls et al, 2022). This study confirms this is also true of Omicron breakthrough infections, with a 153-fold increase in titers to D614G in vaccinated compared to unvaccinated individuals, consistent with other studies (Khan et al, 2022; Suryawanshi et al, 2022; Zhou et al, 2022). We also extend our previous study, where we showed ADCC was boosted by breakthrough infection, to include ADCP, confirming that this applies to other Fc effector functions (Kitchin et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…To our surprise, monovalent Delta RBD-LNP also showed cross-strains immunity against Omicron (Fig 2B). Since a recent study reported that Delta virus infection also induced a cross-variant neutralization of Omicron 16 , it is reasonable to design next generation vaccines based on the Delta RBD sequence. Taken together, our data demonstrated that Omicron-specific mRNA vaccine induced potent neutralizing antibody response against Omicron but not other SARS-CoV-2 variants and lay the foundation for rational development of next generation vaccines against SARS-CoV-2 VOCs.…”
Section: Discussionmentioning
confidence: 99%
“…Only little is known about neutralization profiles of Omicron variant convalescent individuals. (4, 5) So far, either vaccinated individuals after Omicron breakthrough infections or unvaccinated individuals, where the history of previous infection is unknown, were analyzed. Therefore, we analyzed here neutralization profiles against six different SARS-CoV-2 variants for plasma samples from Omicron (BA.1) convalescent individuals with four different combinations of prior SARS-CoV-2 immunity regarding vaccination and previous infection with a non-Omicron variant.…”
Section: Figurementioning
confidence: 99%